Peran Kantor Urusan Agama dalam Meminimalisisr Pernikahan Dini (Studi di Kecamatan Ponggok Kabupaten Blitar) - Rizqi Abdul Latif; Fatimatuz Zahro (MAHAKIM Journal of Islamic Family Law, 2020)
Amendments to Law No. 16 of 2019 concerning changes to the provisions for the age limit of marriage, which were originally stipulated in the 1974 Law Article 7 paragraph 1 for women at least 16 years old and 19 years old for men to marry has now changed to 19 years for men. and women. The Office of Religious Affairs in Ponggok District has implemented a marriage age limit in accordance with Law No. 16 of 2019, which is 19 years for men and women, however the impact of this has resulted in an increase in potential partners who are still underage. This is influenced by the prospective couples who are already pregnant and some of them are sure to get married and have the blessing of their parents. The efforts made by the Ponggok District KUA in minimizing early marriage in its working area are by providing insight into the consequences of early marriage and providing information on the latest Law on community social activities such as yasinan and tahlilan. The purpose of this study was to determine the role and efforts of the Office of Religious Affairs in Ponggok District in minimizing early marriage after the amendment of law No.16 of 2019. In this study the approach used was a qualitative research method. This study uses primary data, namely the interviewer meets directly with the source. Qualitative research is research that intends to understand the phenomena experienced by research subjects. From this research it is known that the KUA of Ponggok sub-district also plays an important role in minimizing early marriage, which is playing a role in administrative matters such as checking the requirements for a prospective partner to marry, if the age is not sufficient then the KUA will reject.